Law Enforcement of Political Corruption (Law Research Review Quarterly, 2018)
Political corruption is an abuse of authority and position by political elites, both those in the parliament and the executive, as well as the core management. Law enforcement using the Corruption Law is unable to touch Political Parties as legal subjects. For this reason, it is necessary to regulate more explicit campaign funds, because one source of political corruption is the amount of political funds to campaign.